Murder in Pitigliano - Trinchieri, Camilla (Trinchieri, Camilla. Tuscan mysteries., 2025)
"Ex-NYPD detective Nico Doyle finds himself unwittingly stepping into the role of a PI to investigate a murder that has torn a young family apart in this rustic mystery set in the beautiful Medieval village of Pitigliano, Italy. One morning at the café, Nico notices Cilia, a seven-year-old girl he has never seen before, playing with OneWag on the floor. He later discovers she has left a note in the dog's collar--Please help my babbo. With help from Daniele of the local carabinieri, Nico discovers that Cilia's father, Saverio, has fled town following an unfortunate incident. His business partner was killed at their electronics store, and Saverio is the main suspect. Cilia's mother, who just moved to Gravigna to get away from Pitigliano's wagging tongues, asks Nico to find the real killer. Against his better judgment, Nico accepts for Cilia's sake and soon finds himself tangling with a large cast of suspects and an unhelpful local carabinier as he pursues the truth"--